Fine needle aspiration cytology of a subcutaneous granular cell tumor - Vikas, S Kavishwar; Vyankatesh, T Anchinmane (Bangladesh Journal of Pathology, 2010)
Key words: fine needle aspiration cytology; granula cell tumor; thigh DOI: 10.3329/bjpath.v25i1.4128 Bangladesh J Pathol 25(1): 23-24